2003
DOI: 10.1172/jci200315937
|View full text |Cite
|
Sign up to set email alerts
|

Novel transglutaminase inhibitors reverse the inflammation of allergic conjunctivitis

Abstract: 2 ), including uteroglobin and lipocortin-1 (annexin I). Uteroglobin and lipocortin-1 retain several conserved sequences. Based on these sequences, several nonapeptides (antiflammins) were synthesized. These nonapeptides were shown to have anti-inflammatory effects in vitro and in vivo, possibly by inhibiting PLA 2 . Subsequent research showed that PLA 2 is activated by transglutaminase 2 (TGase 2). We hypothesize here that TGase 2 inhibitors may increase the anti-inflammatory efficacy of inhibiting PLA 2 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Peptides derived from uteroglobin are among the most potent anti-inflammatory agents identified to date [16]. Recently, a peptide of this kind was successfully tested in an animal model of allergic conjunctivitis [17]. The relevance of these anti-inflammatory effects is supported by decreased local expression of uteroglobin protein in asthma [18].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides derived from uteroglobin are among the most potent anti-inflammatory agents identified to date [16]. Recently, a peptide of this kind was successfully tested in an animal model of allergic conjunctivitis [17]. The relevance of these anti-inflammatory effects is supported by decreased local expression of uteroglobin protein in asthma [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TG2 is abundantly expressed in endothelial cells, macrophages, and smooth muscle cells, 9 and that it is involved in several inflammatory diseases, such as celiac disease, arthritis, and lupus 10 . Once activated by tissue injury, TG2 induces inflammatory and fibrogenic responses 11‐15 . Although the expression of TG2 is upregulated by Th2 cytokines in M2 macrophages, 16 little is known about the role of TG2 in macrophage activation in asthmatic airways.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect evidence of TG2 involvement in inflammation was provided by several studies using inflammatory disease models. Two reports have shown decreased inflammation in animal models of allergic conjunctivitis [ 124 ] and lipopolysaccharide (LPS)-induced lung inflammation [ 125 ], upon treatment with octapeptide R2 (KVLDGQDP) targeting TGase activity. In allergic asthma models, TG2 induced the expression of numerous signaling molecules associated with airway inflammation and remodeling [ 126 ].…”
Section: Tg2 In Immune Cellsmentioning
confidence: 99%